2009
DOI: 10.1128/jvi.00023-08
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA Analog Poly(I:C) Inhibits Human Immunodeficiency Virus Amplification in Dendritic Cells via Type I Interferon-Mediated Activation of APOBEC3G

Abstract: Human immunodeficiency virus (HIV) is taken up by and replicates in immature dendritic cells (imDCs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 78 publications
10
79
1
Order By: Relevance
“…S6) by flow cytometry and found that groups 3 and 5 had higher A3G + cell percentages mostly in monocytes and DCs and only a small proportion (less than onethird) in the CD4 + T-cell compartment. In contrast to T cells (32), monocytes and DCs express primarily the protective low molecular mass (LMM) form of A3G (20,33,34). Significant inverse correlations were observed between the A3G expression increase and the set-point plasma (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…S6) by flow cytometry and found that groups 3 and 5 had higher A3G + cell percentages mostly in monocytes and DCs and only a small proportion (less than onethird) in the CD4 + T-cell compartment. In contrast to T cells (32), monocytes and DCs express primarily the protective low molecular mass (LMM) form of A3G (20,33,34). Significant inverse correlations were observed between the A3G expression increase and the set-point plasma (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, mucosal immunization led to persistent expression of A3G in macaques (19). PolyI:C, one component of our vaccine adjuvant, was reported to inhibit HIV amplification in DCs via A3G induction (20). In the current macaque study, we demonstrated an innate mechanism by which adjuvants may contribute to viral control, and identified candidate adaptive immune correlates of protection.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…However, two studies in primary cells are at odds with findings in 293T cells. One reported that A3A inhibits HIV-1 replication in monocytes (51), whereas the other reported that A3A expression correlates with inhibition of HIV-1 replication in dendritic cells (53). Neither study addressed the mechanism by which A3A could inhibit HIV-1 replication in these primary cell types, given that A3A is not properly packaged into the HIV-1 core.…”
Section: Discussionmentioning
confidence: 91%
“…Others have noted that use of this antiserum results in detection of two ϳ20-kDa A3 proteins in dendritic cells and monocytes (47,53). Although these proteins were initially described as possible A3G degradation products (53), a subsequent publication (47) noted that they are likely to represent APOBEC3A (A3A), an A3 protein that contains only a single deaminase domain and shares 27 of its 29 C-terminal amino acids with A3G.…”
Section: Tc-but Not Cc-specific Deaminase Activity Is Induced In Pbmcmentioning
confidence: 99%